ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DITINJAU DARI MINAT BELAJAR SISWA KELAS XII DI SMA CENDEKIA PASAMAN BARAT - Refi Desmi; Yulia Haryono; Melisa Melisa (IKIP Siliwangi, 2023)
The aim of the research is to analyze and describe the ability to understand mathematical concepts in terms of students' learning interests. The subjects of this study were class XII students at SMA Cendekia Pasaman Barat. This research method is descriptive quantitative. The instruments used were interest in learning questionnaires, test questions, and interview guidelines. The results of the interest in learning questionnaire were analyzed by grouping them into high, medium and low, the test results were analyzed based on indicators of conceptual understanding and interview results. The data analysis technique used in this study was descriptive statistical analysis. The results showed that students with high learning interest had high ability to understand mathematical concepts, then students with moderate and low learning interest had medium and low ability to understand mathematical concepts. Students who have high ability to understand mathematical concepts are able to achieve all indicators of understanding concepts with few errors, then students with moderate and low ability to understand mathematical concepts are unable to meet the indicators of restating a concept and applying concepts or solving algorithms.